Problematika posuzování vad a poruch staveb - Šmahel, Milan (Vysoké učení technické v Brně, Ústav soudního inženýrství, 2015)
Submission of expert reports in litigation concerning the application of discount on previously purchased old real property due to subsequently discovered construction defects and failures led the author to write this contribution. An expert can be given various tasks in the area of this issue, for example, of specifying and determining: whether by the takeover date of real property by a buyer subject properties embodied defects and failures which the buyer had pointed out to a seller. Then, what costs the buyer must spend on removing subject defects and failures, whether defects and failures are caused by a common wear and tear of an object or by something else, and whether and which of the defects and failures originated from an old and worn object. Moreover, whether such wear and tear, with regard to a life span of individual construction components, was common or not and whether (by the takeover date) the objects were suitable for the use and purpose which they were intended (e.g. housing) for. Last but not least, whether it is possible to specify apparent defects and latent defects by discovered defects and failures, to determine price for real property by the sale date, including both determined price according to the price regulation and common price. Simultaneously, the expert can be given the task to express his view on expert reports attached to a file. Both a great number of tasks and a great number of discovered defects and failures mean a big amount of demanding work for experts. It is appropriate to deal with such work systematically right from the beginning so that conducted analyses, final defining of individual pointed defects and failures and final answers are factual, clear and in order. The author’s experience with the issue of dealing with reports in this area is the subject of this contribution.

Ke zpracování tohoto příspěvku autora vedlo podání znaleckých posudků v soudních sporech ve věci uplatnění slevy z ceny již zakoupené starší nemovité věci z důvodu dodatečně zjištěných vad a poruch stavby. V oblasti této problematiky může znalec dostat za úkol například, stanovit nebo určit: zda předmětné nemovitosti vykazovaly ke dni převzetí nemovité věci kupujícím vady a poruchy, které kupující vytkl prodávajícímu, jaké náklady musí kupující vynaložit na odstranění předmětných vad a poruch, zda vady a poruchy mají původ v běžném opotřebení objektu, nebo v jiných příčinách, zda a které z vad a poruch měly svůj původ ve stáří a opotřebení objektu, zda toto opotřebení - s ohledem na životnost jednotlivých stavebních prvků bylo běžné či nikoliv, zda objekty byly (ke dni převzetí) způsobilé k užívání a k účelu, pro který byly určeny (např. bydlení), zda lze u zjištěných vad a poruch stanovit vady zjevné a vady skryté, cenu nemovité věci ke dni prodeje a to jak cenu zjištěnou dle cenového předpisu, tak cenu obvyklou. Současně může znalec dostat za úkol vyjádřit se ke znaleckým posudkům, založeným ve spise. Velké množství úkolů a současně velké množství zjištěných vad a poruch pak představují pro znalce i velké množství náročné práce, ke které je vhodné od samého počátku přistupovat systematicky tak, aby vypracované analýzy, výsledná posouzení jednotlivých vytčených vad a poruch i závěrečné odpovědi byly věcné, srozumitelné a přehledné. Zkušenosti autora s problematikou řešení posudků v této oblasti jsou předmětem tohoto příspěvku.
Issue of defining construction defects and failures
Keywords: defect; apparent defect; latent defect; failure; apparent failure; latent failure; age; life span; estimated life span; common wear and tear; litigation; expert report; Vada; vada zjevná; vada skrytá; porucha; porucha zjevná; porucha skrytá; stáří; životnost; předpokládaná životnost; opotřebení; běžné opotřebení; soudní spor; znalecký posudek